STUDI KOMPARASI SAMINISME DENGAN JEAN PAUL SARTRE TENTANG KEBEBASAN (Tinjauan Filsafat Sosial) - Trisnova, Restu (Jurnal Filsafat "WISDOM", 2010)
The comparative study between Saminism concept and Jean Paul Sartre thought of freedom are: 1) Human freedom, according to Sartre, is an absolute freedom. No other rules which are able to determine human either God or other people; 2) The Saminism concept of freedom is an individual freedom. It means every individual as a subject is able to decide their own choice. Every individual as a subject is independent without any outside order; 3) Saminism freedom conveys individual responsibility. It means every person’s freedom has individual responsibility. Every doer subject can decide everything based on their interest. Therefore, the freedom and responsibility in Saminism actualizes the Jean Paul Sartre thought of freedom.